Self-directed flourishing: a conceptual meta-framework for dealing with the challenges of 21st-century learning and education - Eri Mountbatten-O’Malley; Thomas Howard Morris (Quality Education for All)
Purpose – This paper aims to address the concern that humans are experiencing unprecedented, rapidly changing conditions, in part exacerbated by a recent pandemic, digitization and ongoing wartime. Design/methodology/approach – A paper that seeks to address what the authors are calling the “Educational Malaise”. The authors achieve this through a conceptual and theoretical exploration of the social nature of human beings and learning in the context of readings of human nature, and moral and rational powers. Findings – It is proposed that education should be designed to empower learners to meet the demands of rapidly changing conditions. The ability to adapt is of primary importance for meeting the demands of the changing world, and the “Self-Directed Flourishing” meta-framework can help educators to meet this challenge. Originality/value – Using conceptual and theoretical lenses, in this paper, the authors identify some core problems with traditional pedagogies in formal education and advance a person-centred, humanistic approach to pedagogy. The authors advocate for a new meta-framework for educators: “Self-Directed Flourishing”. The authors propose placing co-creation, courage and conceptual insight at the heart of educational policies and practices, which the authors suggest will nurture a dynamic, adaptable and ethical microculture for human flourishing in 21st-century education and beyond.